Rancang Bangun Alat Eliminasi Gas Buang Menggunakan Mekanisme Ejektor - Saini, Makmur; Nur, Rusdi; Sattar, Sattar; Ibrahim, Ibrahim (Politeknik Negeri Ujung Pandang, 2017)
Environmental pollution (pollutants) can be caused by natural events or human care through uncontrolled industrial and technological activities, this can be a threat to living things including humans in the future. This phenomenon is caused by the entry of particles or chemical substances that do not exist in the natural component so that it exceeds the amount that should be. Pollution is the inclusion of substances, energy and aliens into the environment so that the quality of the environment decreases and no longer suitable allocation. Efforts to reduce or control environmental pollution that some environmental scientists and practitioners have done in a better way by the structures produced by various industries and technologies that are seen as backbones. The research installation can provide detailed information about the shape and structure of the current in the pipe (analogized as the exhaust) in the direction and the vertical velocity to air will be inhaled by the fluid of the liquid (air) as motive fluid in the opposite direction. The suction strength of the liquid against the airflow is greatly determined by the vacuum pressure in the chamber because of the effect of the working ejector that is geometrically formed so that the image can be adjusted to that achievement. The parameters used to measure performance in the design of this air-contaminating air-conditioning installation plant are composed of several variables in the ratio of changes between air velocity and liquid flow in opposite directions, vacuum compressions are formed large enough, the fluid flow capacity of the ejector, revascular and the ability to transform gas pollutants into liquid pollutants.